Association between mental disorders and COVID-19 outcomes among inpatients in France: A retrospective nationwide population-based study. (November 2022) - Descamps, Alexandre; Frenkiel, Jérôme; Zarca, Kevin; Laidi, Charles; Godin, Ophélia; Launay, Odile; Leboyer, Marion; Durand-Zaleski, Isabelle
Abstract: Background: Mental disorders are at-risk of severe COVID-19 outcomes. There is limited and heterogeneous national data in hospital settings evaluating the risks associated with any pre-existing mental disorder, and susceptible subgroups. Our study aimed to investigate the association between pre-existing psychiatric disorders and outcomes of adults hospitalised for COVID-19. Method: We used data obtained from the French national hospital database linked to the state-level psychiatric registry. The primary outcome was 30-days in-hospital mortality. Secondary outcomes were to compare the length of hospital stay, Intensive Care Unit (ICU) admission and ICU length. Propensity score matching analysis was used to control for COVID-19 confounding factors between patients with or without mental disorder and stratified by psychiatric subgroups. Results: Among 97 302 adults hospitalised for COVID-19 from March to September 2020, 10 083 (10.3%) had a pre-existing mental disorder, mainly dementia (3581 [35.5%]), mood disorders (1298 [12.9%]), anxiety disorders (995 [9.9%]), psychoactive substance use disorders (960 [9.5%]), and psychotic disorders (866 [8.6%]). In propensity-matched analysis, 30-days in-hospital mortality was increased among those with at least one pre-existing mental disorder (hazard ratio (HR) 1.15, 95% CI 1.08–1.23), psychotic disorder (1.90, 1.24–2.90), and psychoactive substance disorders (1.53, 1.10–2.14). The odds of ICU admission were consistently decreased for patients with any pre-existing mental disorder (OR 0.83, 95% CI 0.76–0.92) and for those with dementia (0.64, 0.53–0.76). Conclusion: Pre-existing mental disorders were independently associated with in-hospital mortality. These findings underscore the important need for adequate care and targeted interventions for at-risk individuals with severe mental illness.